(3HTGQI GdbOjS GdLjd dhbG GdQShds - (3GdbOjS dhbGs
(3ChdgG (B:s
(3deG cGf cKjQhf bOeG QShkG eTJedkG Ydi GdCTjGA GdeJMbbI ajfG s
(3BNQgG (B:s
(3hYGOhG Edi ChQTdje HaQM YXje hcGfhG ai Gdgjcd cd hbJ jSLhf hjHGQchf Gddg Bejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdOjGfGJ GdCNQis